2019
DOI: 10.1007/s10943-019-00876-w
|View full text |Cite|
|
Sign up to set email alerts
|

Belief, Behavior, and Belonging: How Faith is Indispensable in Preventing and Recovering from Substance Abuse

Abstract: This study reviews the voluminous empirical evidence on faith’s contribution to preventing people from falling victim to substance abuse and helping them recover from it. We find that 73% of addiction treatment programs in the USA include a spirituality-based element, as embodied in the 12-step programs and fellowships initially popularized by Alcoholics Anonymous, the vast majority of which emphasize reliance on God or a Higher Power to stay sober. We introduce and flesh out a typology of faith-based substanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 94 publications
4
69
1
1
Order By: Relevance
“…This finding indicates a need to routinely measure the initial levels of these variables during admission to alcohol addiction treatment to build a robust basis for subsequent practice. This is in accordance with the recommendations of many scholars and clinicians (Grim and Grim 2019 ; Hodge 2001 ) as well as with professional guidelines for therapists (e.g., Association for Spiritual, Ethical, and Religious Values in Counseling 2009 ) and codes of ethics (e.g., American Counseling Association 2014 ). However, although many mental health professionals have acknowledged the benefits of incorporating clients’ spirituality in treatment, it is still not a standard practice in therapy.…”
Section: Discussionsupporting
confidence: 84%
“…This finding indicates a need to routinely measure the initial levels of these variables during admission to alcohol addiction treatment to build a robust basis for subsequent practice. This is in accordance with the recommendations of many scholars and clinicians (Grim and Grim 2019 ; Hodge 2001 ) as well as with professional guidelines for therapists (e.g., Association for Spiritual, Ethical, and Religious Values in Counseling 2009 ) and codes of ethics (e.g., American Counseling Association 2014 ). However, although many mental health professionals have acknowledged the benefits of incorporating clients’ spirituality in treatment, it is still not a standard practice in therapy.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have identified religiosity and spirituality as protective factors against the development of substance and behavioral addictions (Bliss 2007;Clarke et al 2006;Cook 2004;Grim and Grim 2019;Shim 2019). Most religions (which may serve as a conduit to transcendent experience; Oman 2013) include explicit proscriptions against risky behaviors, encourage people to work on self-control to show more resistance to urges and temptations (Carter et al 2012), and teach about the importance of taking care of body, mind, and spirit.…”
Section: Spirituality and Shopping Addictionmentioning
confidence: 99%
“…Spirituality and religion are well-documented and essential components of prevention, treatment, and recovery of substance use disorders (Beraldo et al, 2019 ; Grim & Grim, 2019 ; Walton-Moss et al, 2013 ). Religious beliefs, affiliation, and valuing spirituality are associated with lower propensity to engage in substance use across a range of studies and populations (e.g., Brown et al, 2013 ; Gorsuch, 1995 ; Leigh et al, 2005 ; Marsiglia et al, 2005 ).…”
Section: Background and Study Purposementioning
confidence: 99%
“…Faith communities are in a distinct position to help individuals, families, and communities in supporting recovery and resilience of substance use disorders—particularly in times of crisis. Grim and Grim ( 2019 ) argued: “In addition to the efficacious role of spirituality, congregations and faith-based institutions are particularly effective in community mobilization and timely response to crises. Faith communities are adept at facilitating quality group interactions focused on overcoming past negative experiences, which are often drivers of the emotional and spiritual despondency that feed mental illness and substance abuse” (p. 1737).…”
Section: Background and Study Purposementioning
confidence: 99%
See 1 more Smart Citation